DEVELOPMENT AND EVALUATION OF MOUTH DISSOLVING FILM OF DEXTROMETHORPHAN HYDROBROMIDE AND CHLORPHENIRAMINE MALEATE (KSV Journal of Pharmacy and Health Sciences, 2025)
The combination of dextromethorphan (DXM) and chlorpheniramine maleate (CPM) offers a robust therapeutic strategy for managing cough and allergic symptoms, grounded in their complementary pharmacological mechanisms. The objective of the present investigation was to formulate a mouth dissolving film for the drug combination. A further objective was to mask the bitter taste of the drugs. Simultaneous equation method was used for analysis of the two drugs as they show absorbance at λmax of each other. Film was formulated using hydroxypropyl methyl cellulose E5 as film former and polyethylene glycol 400 as plasticizer. Face-centered factorial design was applied to optimize the amount of polymer and plasticizer so as to get high folding endurance coupled with minimum disintegration time.  First order model for folding endurance and perfect quadratic model were selected for disintegration time. Mathematical models were generated for folding endurance and disintegration time. Contour plots were generated for both the response and overlayed to identify the desirable zone. Checkpoint batch was identified and the selected combination was used to prepare the film. The observed value was in agreement with the predicted value. This formulation was taken forward for taste masking using Sucralose and Aspartame. The final formulation was tested for taste masking using Brief Access Taste Aversion model which indicated better acceptance of formulation as compared to plain drug solution. The formulation was found to be stable over a period of 1 month at ambient conditions.